A obesidade em camundongos C57BL/6 altera as células da imunidade inata na infecção por Leishmania major - Vinicius Dantas Martins (2019)
Obesity is a health problem related to metabolic and immunological disorders. It is also related to low grade inflammation and lead to increased susceptibility to infectious diseases. In our previous work, we have shown that C57BL/6 mice with diet induced obesity were more susceptible to L. major infection. In this study, we sought to understand the mechanism involved in this increasing susceptibility in obese animals. C57BL/6 mice were fed a high-calorie diet containing high-fat lipids (butter) and carbohydrates (refined sugar) called HSB (high sugar butter) or control diet (AIN93-G) for 12 weeks. After 12 weeks, the mice showed difference in weight gain and were infected with Leishmania major promastigotes. First, we confirmed that obesity lead to increasing lesion size and higher parasite burden after 8 weeks of infection. To assess the effect of obesity on innate immunity during L. major infection, neutrophil (Ne), monocytes (Mo) and macrophages (Mφ) frequencies from blood, adipose tissue, spleen and ears were analyzed using flow cytometry after 2 days and 8 weeks post infection. Before infection, obese mice had a higher frequency of Ne, Mo and Mφ in the blood and a higher frequency of Mφ and Mo in the adipose tissue than the control mice. We did not observe any difference between populations of spleen cells and only a few leukocytes were found in the ear before infection. Two days after infection, there was no change in the cells analyzed in the spleen and adipose tissue. Obese infected mice had a smaller Ne infiltrate in the infected ear when compared to infected control mice. Despite presenting more circulating Ne and Mo, obese animals were unable to recruit the cells into the skin after 2 days of infection. In the chronic period of infection (8 weeks), we observed an increase in myeloid cells (Mo and Mφ) with anti-inflammatory signature in the spleen (CD11b+ CD206+) and at the site of infection (CD11b+Ly6CintCD206+), suggesting that obesity changes profile of cells in the lesion and elevates the frequency of macrophages that may have an ineffective profile in the control of L. major compatible with resistance to the parasite.